Information Society - Creation of a Cloud Portal for Information System using CASE and AI Technologies - Surguladze, Gia; Topuria, Nino; Kashibadze, Marina (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
The innovative role of ICT in the process of forming Information Society in the sustainable development of legal, technical-economic, ecological and socio-cultural spheres is discussed. A methodology developed at the Department of Software Engineering of GTU is proposed for the automation of the processes of designing and programming modern information systems. In particular, in accordance with the stages of the life cycle of creating software for a design object, a functional user web portal is created using CASE technologies and artificial intelligence methods based on client-server and service-oriented architecture using Azure SQL Server and hybrid programming technologies (WCF/WPF). Illustrative practical examples are discussed for education, Black Sea eco-monitoring, multimodal transportation logistics management, etc. systems.